En live sur Pitchfork : les performances multiples de la forme audiovisuelle - Maxim Bonin (Communiquer)
Based on a documentary analysis of audiovisual productions posted online on Pitchfork and the content that promotes it, this article explores how the use of live music allows the webzine to legitimize its role as a creative component within the music industries. How have the molding forces of digital platforms, such as YouTube, transformed the webzine’s practices and the possibilities for creating and broadcasting live audiovisual productions? This article proposes the concept of form performance by exploring how multiple performances can be attributed to a given cultural form.